Spatial response of Medicago truncatula plants to drought and spider mite attack - Antoniou, Chrystalla; Fragkoudi, Ioanna; Martinou, Angeliki F.; Stavrinides, Menelaos; Fotopoulos, Vasileios (My University, 2018)
Plant response to imposition of biotic and abiotic stresses by inducing their defense mechanisms, with the production of reactive oxygen species (ROS) representing a major defense response. The present work examined the simultaneous impact of two key stress factors, drought and spider mite attack (Tetranychus urticae) in Medicago truncatula plants. Hydrogen peroxide (H2O2), lipid peroxidation (MDA content) and proline content in well-watered and drought-stressed leaves infested by spider mites along with neighboring leaves were examined in order to investigate the local and systemic effect of the two stresses on the antioxidant and osmoprotective response. High levels of lipid peroxidation were recorded in plants under drought stress and plants under combined drought stress and spider mite feeding compared with control plants. Hydrogen peroxide biosynthesis was significantly induced in plants under drought and spider mite attack, with highest levels detected in the feeding leaf (local response). Proline was accumulated in drought stressed-plants, with the highest levels observed in plants exposed to a combination of drought stress and mite feeding. RT-qPCR expression analysis of key genes implicated in ROS metabolism (PAO, DAO, AOX, CuZnSOD, FeSOD, MnSOD) and proline biosynthesis (P5CR, P5CS) pointed to different patterns of regulation between abiotic and biotic stress, as well as their combination. Exposure of plants to both drought stress and attack by spider mites mainly affected the local antioxidant and osmoprotective response of Medicago truncatula, highlighting the relative significance of drought-induced phenomena in combined drought/mite infestation stress responses.
Keywords: Biotic stress; Abiotic stress; Spider mites; ROS; Proline; Climate change